1998
DOI: 10.3109/17518429809060945
|View full text |Cite
|
Sign up to set email alerts
|

Intervention approaches and children with developmental coordination disorder

Abstract: Children with Developmental Coordination Disorder (DCD) have a marked impairment in the performance of functional motor skills required to succeed at school. Longitudinal studies show that without intervention children with DCD often do not improve with development and the poor motor behaviour appears to have a detrimental effect on other aspects of functioning such as school achievement, behaviour and self esteem. Outside of clinical situations, there are only a small number of controlled empirical investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 42 publications
0
44
0
5
Order By: Relevance
“…As occupational therapists, we view sensory and perceptual-motor abilities as being important foundational skills for the attainment of end-product abilities (that is, praxis, visual perception, language and articulation abilities, behaviour, activity level, and emotional tone) that are crucial for a child's school performance (Royeen & Marsh, 1988;Dunn, 1992;Duncan, 1998;Parham, 1998;Spitzer & Roley, 2001). The correlations that exist between these sensory-motor-perceptual abilities and school performance have been well verified in the scientific literature (Polatajko et al, 1991;Taylor et al, 1995;Fletcher-Flinn et al, 1997;Sugden and Chambers, 1998;Haskell, 2000;Rosenbaum et al, 2001), and in addition, research has shown that skill level in these areas can reliably discriminate between children with and without learning impairments (Rosenberg, 1989;Chiarenza, 1990;Murray et al, 1990;Fisher and Murray, 1991;Summerfield & Michie, 1993).…”
Section: Introductionmentioning
confidence: 88%
“…As occupational therapists, we view sensory and perceptual-motor abilities as being important foundational skills for the attainment of end-product abilities (that is, praxis, visual perception, language and articulation abilities, behaviour, activity level, and emotional tone) that are crucial for a child's school performance (Royeen & Marsh, 1988;Dunn, 1992;Duncan, 1998;Parham, 1998;Spitzer & Roley, 2001). The correlations that exist between these sensory-motor-perceptual abilities and school performance have been well verified in the scientific literature (Polatajko et al, 1991;Taylor et al, 1995;Fletcher-Flinn et al, 1997;Sugden and Chambers, 1998;Haskell, 2000;Rosenbaum et al, 2001), and in addition, research has shown that skill level in these areas can reliably discriminate between children with and without learning impairments (Rosenberg, 1989;Chiarenza, 1990;Murray et al, 1990;Fisher and Murray, 1991;Summerfield & Michie, 1993).…”
Section: Introductionmentioning
confidence: 88%
“…Kinder mit motorischen Entwicklungsstörungen oder Behinderungen weisen sowohl im Bereich der Fähigkeiten als auch der Fertigkeiten motorische Einschränkungen auf. > Bei kombinierten Entwicklungsstörungen sind schulische, emotionale und soziale Probleme häufig Die Frage, ob motorische Entwicklungsstörungen mit Lernstörungen und Verhaltensauffälligkeiten einhergehen, wird kontrovers diskutiert [5,6,23]. Bei Kindern mit isolierten umschriebenen Entwicklungsstörungen der Motorik ergaben sich auf Datenbasis der Kurpfalzstudie [5] als Längsschnittstudie keine Hinweise auf Stö-rungen der kognitiven Leistungsfähigkeit und Schulentwicklung, bei jedoch leicht erhöhter Rate an emotionalen Auffälligkeiten.…”
Section: Motorische Fähig-und Fertigkeiten Entwicklungsstörungen Undunclassified
“…There is a body of literature that can point to success in intervention. [41][42][43] So far, there have been two major approaches to intervention, under different labels, but often referred to as either process-oriented or task-oriented approaches.…”
Section: What Do We Know About Intervention?mentioning
confidence: 99%